Synthesis and charaterization of magnesium zinc ferrites as electromagnetic source - Yahya, Noorhana; Mohamad Nor Aripin, Ami Salwani; A. Aziz, Azizuddin; Daud, Hanita; Mohd Zaid, Hasnah; Lim, Kean Pah; Maarof, Norehan (Science Publications, 2008)
Fabrication of Mg1-XZnXFe2O4 (where x = 0.2, 0.3, 0.4 and 0.5) samples using a conventional technique is reported. Oxides of magnesium, zinc and iron with purity of about 99.99% were mixed with distilled water in a milling machine for 12 hours. They were then filtered and presintered at 1250°C and sintered at 1350°C for 10 h in air. The phase and the crystal structure of the asprepared samples were identified using X-Ray Diffraction analysis (XRD). Hysteresis graph was evaluated using Vibrating Sample Magnetometer (VSM) to get the saturation magnetization (emu g-1)and coercivity (G) value. Atomic Force Microscope (AFM) was used to observe the surface morphology. The X-ray diffraction analysis showed major peak at plane (3 1 1) of the cubic structure for all the ferrites. The largest value of density achieved was 4.69 gcm-3 which was exhibited by sample with 0.5 mole fraction of zinc content. Highest saturation magnetization value (3.652emu g-1)was obtained for the 0.3 mole fraction of zinc content. A strong correlation between the saturation magnetization and zinc content was observed. We speculate that it is due to the Heisenberg superexchange interaction of magnetic Fe3+ and non-magnetic Zn2+ occupying the tetrahedral sites. The sample was used to induce electromagnetic (EM) waves in high operating frequency (5 MHz).